Pengaruh Daun Kelapa Sawit sebagai Naungan terhadap Pertumbuhan Bibit Kelapa Sawit pada Tahap Pre Nursery - Rufinusta Sinuraya (Politeknik Kelapa Sawit Citra Widya Edukasi, 2019)
The purpose of this research is to know the growth response of oil palm seedlings at pre nursery to the shade treatment of oil palm leaves. Research on the effect of palm oil leaves as a shade on the growth of oil palm seeddlings at the pre nursery stage. Conducted on March 5 until May 28, 2014 at PT Mahakam Sawit Plantation, Tanjung Harapan Village, Sebulu Timur Subdistrict, Kutai Kartanegara, Kalimantan Province, using Randomized Compete Design with a non-factorial design with 2 treatments, each treatment consisted of 6 replications. Thus the number of seeds used as many as 12 seeds of treatment A is without shade (control) and C is the shade of the leaves of oil palm. The parameters observed were seedling height, stem diameter, number of leaves and total leaf area. The results showed that the treatment of shade of oil palm leaves significantly affected the growth of oil palm seedlins with values of seedlings height, stem diameter, number of leaves and total leaf area at 12 week after planting each is 21.50 cm, 0.93 cm, 3.5 strands and 64,75 cm². The shade treatment resulted in significantly different oil palm seedlings growth wit no shade treatment. The shade treatment resulted in seedlings height, stem diameter, number of leaves and total leaf area greater than the treatment without shade with milai difference of 29.86 %, 25.01 %, 14.29 % and 46.64 %.